PULMONARY FUNCTION TESTS IN NATHIAGALI NATIVES - Ayub, Mohammad; Badar, Ahmed; Daud, Mohammad; Yousaf, Mohammad; Khan, Farrukh A; Waqar, Nusrat (Journal of Ayub Medical College Abbottabad, 1998)
To compare the lung function of the people living at low and high altitude, spirometry was performed on 45 clinically healthy male subjects native of Haripur, altitude 530 m. Above Sea Level (ASL) and another 45 male subjects were studied for the same parameters from Nathiagali (altitude 2,530 m. ASL). Their age range was from 21 to 40 years. The spirometric values were significantly higher in the younger subjects from Nathiagali than their counterparts from Haripur. However, the older subjects did not show any significant differences in their spirometric values except in Forced Vital Capacity (FVC), indicating a rapid deterioration in the flow rates and expiratory' timings of the subjects living at Nathiagali. This may probably be explained as to be due to excessive exposure to cold, allergens. possibly micro-organisms and smoke from wood-fire, which produce subclinical bronchitis in this population. Further detailed investigation in the problem to determine the real cause of rapid decline in the lung function of this population is suggested.